WEAVING MEANING: LOCAL KNOWLEDGE REPRESENTATION IN REJANG WASTRA DANCE - Jayantini, I Gusti Agung Sri Rwa; Surata, Sang Putu Kaler; Hikmaharyanti, Putu Desi Anggerina; Jayantiari, I Gusti Agung Mas Rwa; Umbas, Ronald (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
This study investigates the local knowledge represented in the performance of the Rejang Wastra dance, which forms an integral part of Hindu religious ceremonies in Demulih village, Susut subdistrict, Bangli regency, Bali. Respected by the local community, this sacred dance embodies profound symbolic, functional, and philosophical meanings. Using a qualitative approach based on the exploration of traditional dance characteristics, the study reveals two main forms of local wisdom. The first finding shows that the dance represents the traditional market practice before ceremonies, symbolizing interdependence and ritual preparation. The second finding indicates that it illustrates stages of human life in Hindu philosophy, portraying a spiritual journey from birth to unity with the divine. Both meanings express the Balinese concept of Tri Hita Karana, emphasizing harmony among humans, God (Parahyangan), nature (Palemahan), and society (Pawongan). Overall, Rejang Wastra is not only a ritual dance but also a living medium that transmits local knowledge and ethical values, preserving cultural wisdom within Balinese society.